A Need Analysis for Developing Arabic Phonetics: A Strategy for Mastering the Pronunciation of Arabic Letters - rifain, syakirah; Arifin Sapar, Ahmad; Hussin, Mohamad; A.H., Shahidi (Forum for Linguistic Studies, 2024)
Learning the pronunciation of hijaiyyah letters in the Quran is an important element in mastering the Arabic language. This study, therefore, aims to analyse the need for the development of the Aswat Knowledge Model. The method used is qualitative, which is the recording of the pronunciation of hijaiyyah letters by primary school students’ in Petaling Jaya and the teachers’ questionnaire. Recordings were analysed based on expert evaluation and PRAAT software. The findings of the study show that there are nine letters included in the medium category including ظ, ع, ق while the difficult category has five letters including ث, خ, ض. The general method of teaching is through talaqqi musyafahah and explanation. In general, specific teaching techniques related to places of articulation system (makhraj) and manner of articulation system (sifat hurf) are through different methods including the determination of articulation tools, sound methods such as vibration and wind, and so on. PRAAT analysis shows that the vowel pattern of the speaker’s speech is closer to the Malay pattern than the Arabic pattern. The findings of the study show that there is a need to develop a model, which will focus on difficult sounds for Arabic language learners. To use the model effectively, other aspects such as assessing student abilities and choosing appropriate learning materials also need to be taken into account.